Hands-On RESTful Python Web Services Develop RESTful web services or APIs with modern Python 3.7 - Hillar, Gastón C. (Packt, 2018)
bExplore the best tools and techniques to create lightweight, maintainable, and scalable Python web services/b h4Key Features/h4 ulliCombine Python with different data sources to build complex RESTful APIs from scratch /li liConfigure and fine-tune your APIs using the best tools and techniques available /li liUse command-line and GUI tools to test CRUD operations performed by RESTful Web Services or APIs /li /ul h4Book Description/h4 Python is the language of choice for millions of developers worldwide that builds great web services in RESTful architecture. This second edition of Hands-On RESTful Python Web Services will cover the best tools you can use to build engaging web services. This book shows you how to develop RESTful APIs using the most popular Python frameworks and all the necessary stacks with Python, combined with related libraries and tools.
Keywords: COMPUTERS / Web / Web Services & APIs; COMPUTERS / Programming / Object Oriented